Mary's bodily Assumption - Levering, Matthew, 1971- (University of Notre Dame Press, 2015)
In Mary's Bodily Assumption, Matthew Levering presents a contemporary explanation and defense of the Catholic doctrine of Mary's bodily Assumption.
Keywords: Mary, -- Blessed Virgin, Saint -- Assumption.; Catholic Church -- Doctrines.; Marie, -- Sainte Vierge -- Assomption.; Église catholique -- Doctrines.; Mary, -- Blessed Virgin, Saint; Catholic Church; RELIGION -- Christian Theology -- Mariology.; Assumption of the Blessed Virgin Mary; Theology, Doctrinal